Spectral and thermal studies on the synthesis and catalyzed oligomerization of novel cardanol-based benzoxazines. (1st June 2016) - Kotzebue, Lloyd Ryan Viana; Ribeiro, Francisco Wanderson Moreira; Sombra, Venícios Gonçalves; Feitosa, Judith P.A.; Mele, Giuseppe; Mazzetto, Selma Elaine; Lomonaco, Diego
Abstract: The aim of this study was to synthesize novel cardanol-based benzoxazines, using different primary amines, and evaluate their influences on the synthesis and polymerization process. The monomers were characterized using NMR ( 1 H and 13 C), FT-IR, DSC and TGA. It was demonstrated how the amines structures influence on the stability of the oxazine ring, which relates to the onset polymerization temperature (Te ). Aniline-type benzoxazines provided higher Te than aliphatic ones. Since at this elevate temperature (230–295 °C) the alkyl chain of cardanol could degrade, the use of a new catalyst was also evaluated, showing the innocuous MgCl2 as an efficient alternative. The polymerization of these monomers with MgCl2 (1%) were studied using FT-IR, DSC and GPC, showing that under mild temperatures it is possible to obtain polybenzoxazines completely soluble and with high polydispersity. Graphical abstract: Highlights: Novel cardanol-based benzoxazines were synthesized and characterized. The primary amines structure influenced on the stability of the oxazine ring. MgCl2 showed to be an effective catalyst for the polymerization of benzoxazines. GPC showed that polymers was consisted of highly polydispersed oligomers.